Prevalence of alcohol use disorders and associated factors among people with epilepsy attending Amanuel Mental Specialized Hospital, Addis Ababa, Ethiopia - Waja T (Dove Medical Press, 2016)
Tsegereda Waja,1 Jemal Ebrahim,2 Zegeye Yohannis,1 Asres Bedaso2 1Department of Psychiatry, Amanuel Mental Specialized Hospital, Addis Ababa, 2School of Nursing and Midwifery, College of Medicine and Health Sciences, Hawassa University, Hawassa, SNNPR, Ethiopia Introduction: Alcohol use disorders represent one of the leading causes of preventable death, illness, and injury in many societies throughout the world. Heavy alcohol consumption has multiple negative consequences for people with epilepsy such as precipitation of seizure, exacerbation of seizure, poor seizure control, increased side effects of antiepileptic drugs, noncompliance to antiepileptic drugs, alcohol withdrawal seizures, long-term hospital admission, status epilepticus, sudden unexpected death, and premature mortality. Methods: An institution-based cross sectional study was conducted from April 15, 2014 to May 15, 2014 with the aim of assessing prevalence of alcohol use disorders and associated factors among people with epilepsy attending Amanuel Mental Specialized Hospital, Addis Ababa, Ethiopia. A total of 413 randomly selected epileptic patients were included in this study. Data were structured using the 10-item Alcohol Use Disorders Identification questionnaire. Data were analyzed using SPSS Version 20. Bivariate and multivariate logistic regression analyses were performed to study the association, and variables with P-value <0.05 were considered as having a statistically significant association at 95% confidence interval. Results: A total of 423 study participants were selected, of whom 413 completely filled the questionnaire making the response rate 97.6%. The mean age of the respondents was 31.9 years with standard deviation of ±10.97, and 248 (60%) were males. The prevalence of alcohol use disorder was 17.4%. Educational status (grade 9–12) (adjusted odds ratio [AOR] =3.25, [1.21, 8.69]), not living with family members (AOR =1.89, [1.06, 3.39]), availability of house (AOR =2.04, [1.10, 3.78]), taking carbamazepine (AOR =2.38, [1.13, 5.01]), and drinking alcohol to find relief from stress (AOR =4.28, [1.89, 9.67]) were significantly associated with alcohol use disorder among people with epilepsy. Conclusion and recommendation: The findings of this study revealed that the prevalence of alcohol use disorder among people with epilepsy was high. Routine screening of epileptic patients with the Alcohol Use Disorders Identification Test is recommended. Keywords: alcohol use disorder, epilepsy, Amanuel Mental Specialized Hospital, sub-Saharan Africa, stress relief